2008
DOI: 10.1016/j.agrformet.2008.03.004
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of potential yields and yield gaps of rainfed soybean in India using CROPGRO-Soybean model

Abstract: a g r i c u l t u r a l a n d f o r e s t m e t e o r o l o g y 1 4 8 ( 2 0 0 8 ) 1 2 5 2 -1 2 6 5 a r t i c l e i n f o

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
81
0
6

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 139 publications
(90 citation statements)
references
References 9 publications
3
81
0
6
Order By: Relevance
“…High and significant correlation between the seed yield and TIPAR further supports the validity, robustness and generality of the correlation between IPAR and crop growth. The average seed yields of 1.60 t ha -1 for NC and 2.87 t ha -1 for MLBD in both seasons compare well with 2.7 t ha -1 (Bhatia et al, 2008) and 1.7 to 2.3 t ha -1 (Tefera, 2011). It was higher than 2.49 t ha -1 (Adeniyan and Ayoola, 2006) and far above the 1.5 t ha -1 (Akande et al, 2007).…”
Section: Seed Yield Ipar and Ruementioning
confidence: 52%
“…High and significant correlation between the seed yield and TIPAR further supports the validity, robustness and generality of the correlation between IPAR and crop growth. The average seed yields of 1.60 t ha -1 for NC and 2.87 t ha -1 for MLBD in both seasons compare well with 2.7 t ha -1 (Bhatia et al, 2008) and 1.7 to 2.3 t ha -1 (Tefera, 2011). It was higher than 2.49 t ha -1 (Adeniyan and Ayoola, 2006) and far above the 1.5 t ha -1 (Akande et al, 2007).…”
Section: Seed Yield Ipar and Ruementioning
confidence: 52%
“…Simulation study by Bhatia et al, 2008, revealed climatic potential of 30 to 35 qt/ha and rainfed potential of 20 to 25 qt/ha. The study also reported that maximum simulated yield achieved for soybean under water nonlimiting condition was 54 qt/ha in Hosangabad district of Madhya Pradesh, 48.6 qt/ha in Amravati district of Maharashtra, and 46.2 qt/ha at Vidisha district of Madhya Pradesh.…”
Section: Varieties Released and Yield Potentialmentioning
confidence: 99%
“…The CSM-DSSAT models in the DSSAT (v4.0) software package have been tested against various single factors, such as crop yield, soil water, plant-available N, cultivar, planting date and temperature (Boote et al 1998;Alagarswamy et al 2000;Hunt et al 2001;Jones et al 2003;Soler et al 2007;Bhatia et al 2008;Langensiepen et al 2008;Stastna et al 2010;Wang et al 2010). …”
Section: Crop Growth Modelmentioning
confidence: 99%